Factors Affecting the Flight Capacity of Two Woodwasp Species, Sirex noctilio F. (Hymenoptera: Siricidae) and Sirex nitobei M. (Hymenoptera: Siricidae) - Xiaobo Liu; Juan Shi; Lili Ren; Youqing Luo (Insects, 2023)
Sirex noctilio F. is an invasive woodwasp that causes pine mortality in plantations in China. Sirex nitobei M. is a native woodwasp in large areas of China. In this study, the flight capacity of the two woodwasps was studied and compared using a tethered-flight mill system to find individual factors affecting the flight capacity. After flight bioassays, woodwasps were dissected to determine nematode infestation. Post-eclosion-day (PED) age significantly influenced the flight capacity of S. noctilio females and males; as woodwasps become older, their flight capacity decreased. For S. nitobei, PED age did not significantly affect their flight capacity. In general, the flight capacity of S. noctilio was greater than that of S. nitobei. Females flew further and for longer than males for both Sirex species. The Deladenus spp. parasitism status of the two Sirex species did not significantly affect their flight performance parameters. PED age and body mass were key individual factors significantly affecting the flight capacity of the two Sirex species. In this study, detailed and accurate tethered-flight parameters of S. noctilio and S. nitobei were obtained. Although this is different from natural flight, it also provides us substantial laboratory data on their flight capacity, and facilitates risk analysis of the two woodwasp species.